Acute Injuries in Recreational and Competitive Surfers: Incidence, Severity, Location, Type, and Mechanism. (May 2015) - Furness, James; Hing, Wayne; Walsh, Joe; Abbott, Allan; Sheppard, Jeremy M.; Climstein, Mike
Background: There are an estimated 37 million surfers worldwide, with 2.5 million recreational surfers in Australia. The recreational activity and sport of surfing has grown dramatically since the 1960s, but scientific research has been poorly mirrored in comparison with most other mainstream sports. Purpose: To identify the incidence, severity, location, type, and mechanism of acute injuries in recreational and competitive surfers over a 12-month period. Study Design: Descriptive epidemiology study. Methods: An online survey using an open-source survey application was utilized. The survey consisted of 2 primary sections: Section 1 included demographic information and participation levels (age, height, weight, hours surfed, competitive level); section 2 incorporated injury type, mechanism, severity, and injury management. Results: A total of 1348 participants (91.3% males; 43.1% competitive surfers) were included in data analysis. A total of 512 acute injuries were classified as major, providing an incidence proportion of 0.38 (CI, 0.35-0.41) acute injuries per year. The incidence rate was calculated to be 1.79 (CI, 1.67-1.92) major injuries per 1000 hours of surfing. The shoulder, ankle, and head/face regions had the highest frequencies of acute injury, representing 16.4%, 14.6%, and 13.3%, respectively. Injuries were predominantly of muscular, joint, and skin origin, representing 30.3%, 27.7%, and 18.9%, respectively. Skin injuries were primarily a result of direct trauma, while joint and muscular injuries were mainly a result of maneuvers performed and repetitive actions. Key risk factors that increased the incidence of sustaining an acute injury included competitive status, hours surfed (>6.5 hours/week), and the ability to perform aerial maneuvers. The incidence proportion for surfers completing aerial maneuvers was calculated to be 0.48 (CI, 0.39-0.58) major injuries per year, this being the highest incidence proportion irrespective of competitive status. Conclusion: This is the largest surfing-specific survey that included both recreational and competitive surfers conducted in Australia to date. The shoulder, ankle, head, and face were identified as the key regions where acute injuries occur in surfers. This research may aid in reducing the occurrence of injury through musculoskeletal screening in these key injury-prone regions and through the use of sport-specific strength training and conditioning.